MODEL PENYEBARAN PENYAKIT KAKI GAJAH DENGAN PENGARUH PEMBERIAN OBAT PENCEGAHAN MASSAL - Fitria Eka Nurfarida (Jurnal Matematika, 2016)
ABSTRACT. Filariasis is abnormalities in humans caused by filarial worms through the intermediary vector mosquitoes. This final project is modifying a nonlinier system of differential equations that describe mathematical model of spreading filariasis with SSIC model (Susceptible, Susceptible Treated, Infected, Chronic) for human population and SI model (Susceptible, Infected) for vector mosquitos population, with giving preventive medicine POPM into susceptible human.Keywords : Filariasis, Model SSIC-SI, Prevention, POPM